Comparison of the electrochemical performance of iron hexacyanoferrate with high and low quality as cathode materials for aqueous sodium-ion batteries. Issue 50 (9th June 2017) - Cai, Daoping; Yang, Xuhui; Qu, Baihua; Wang, Taihong
Abstract : High quality iron hexacyanoferrate nanocubes (HQ-PB NCs) were synthesized, which exhibited excellent electrochemical performance as cathode materials for aqueous sodium-ion batteries. Abstract : In this work, high quality iron hexacyanoferrate nanocubes (HQ-PB NCs) were synthesized through a simple hydrothermal method and then investigated as cathode electrode materials for aqueous sodium-ion batteries (SIBs), which displayed a much enhanced electrochemical performance compared with the PB nanoparticles with low quality (LQ-PB NPs). The HQ-PB NCs could be promising cathode materials for aqueous SIBs.